2016
DOI: 10.1016/j.neuroimage.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Glucose consumption of inflammatory cells masks metabolic deficits in the brain

Abstract: Inflammatory cells such as microglia need energy to exert their functions and to maintain their cellular integrity and membrane potential. Subsequent to cerebral ischemia, inflammatory cells infiltrate tissue with limited blood flow where neurons and astrocytes died due to insufficient supply with oxygen and glucose. Using dual tracer positron emission tomography (PET), we found that concomitant with the presence of inflammatory cells, transport and consumption of glucose increased up to normal levels but retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…At least in human neurodegenerative disease, there is an inverse relationship between cortical TSPO binding and 18 F-FDG uptake (34). However, PET studies do not distinguish the cellular site of TSPO binding or metabolism; another investigation suggests that glucose consumption of inflammatory cells could mask the true extent of specifically neuronal metabolism deficits in the aging brain (11). In regional analysis of our WT mice, we confirmed a high spatial similarity by the calculated Sørensen-Dice coefficient (54.5%), which fits to the proposed colocalization of the increases in the 2 markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in human neurodegenerative disease, there is an inverse relationship between cortical TSPO binding and 18 F-FDG uptake (34). However, PET studies do not distinguish the cellular site of TSPO binding or metabolism; another investigation suggests that glucose consumption of inflammatory cells could mask the true extent of specifically neuronal metabolism deficits in the aging brain (11). In regional analysis of our WT mice, we confirmed a high spatial similarity by the calculated Sørensen-Dice coefficient (54.5%), which fits to the proposed colocalization of the increases in the 2 markers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the established findings of agerelated hypometabolism in the healthy human brain, previous preclinical studies found glucose hypermetabolism in aged wild-type (WT) mice relative to younger animals (9,10). Microglial activation has been suggested as a possible driver for age-related 18 F-FDG hypermetabolism in mice (11). To test this hypothesis, we earlier undertook a dual-tracer small-animal PET study with 18 F-FDG and also 18 F-GE180, a tracer for the 18-kDa translocator protein (TSPO), which is highly expressed at the outer mitochondrial membrane of activated microglia; preliminary results indicated an association between aged-dependent parallel increases in TSPO binding and 18 F-FDG uptake in a transgenic AD model and also WT mice (12).…”
mentioning
confidence: 85%
“…At present, little is known about the link between microglia bioenergetics, neuroinflammation, and brain energy failure in AD neurodegeneration. Recently, sophisticated neuroimaging studies using multiple-tracer PET revealed the apparent coexistence of neuroinflammation and elevated glucose consumption in animal models of AD pathology and brain ischemia [105,106]. This may seem paradoxical as it has been consistently demonstrated that glucose hypometabolism is a disease marker of the AD brain.…”
Section: Microglial Metabolism and Neurodegenerative Disordersmentioning
confidence: 99%
“…This may seem paradoxical as it has been consistently demonstrated that glucose hypometabolism is a disease marker of the AD brain. Backes et al [105] claimed that inflammatory cells in diseased brains managed to consume comparable amounts of glucose per time and tissue volume as neurons and astrocytes consume during healthy conditions. Given that brain immune cells are capable of harvesting high amounts of glucose and nonoxidatively metabolize the substrate in reduced oxygen and glucose conditions, those observations suggest that energy metabolism of brain inflammatory cells (including microglia) may be masking metabolic deficits in regions with neuronal damage.…”
Section: Microglial Metabolism and Neurodegenerative Disordersmentioning
confidence: 99%
“…Overall, the available data show topographical concordance between these biomarkers, with neuroimmune activation detected by PET in AD- and Parkinson's disease and dementia–associated hypometabolic regions and beyond [47] , [48] , [49] , [50] , possibly predicting the severity of metabolic decline at follow-up [48] . On a technical note, multimodal neuroinflammation/glucose metabolism studies could be partially biased by the locally activated immune cells that by increasing their glucose utilization may attenuate the local cerebral hypometabolism detected by 18 F-FDG-PET [51] .…”
Section: Introductionmentioning
confidence: 99%